Fragmentation and clustering in vertically linked industries - Pais, Joana (2022)
This paper models the location of two vertically related firms in a low labor cost country and in a country with a large market. The upstream industry is more labor intensive than the downstream industry. We find that spatial fragmentation occurs for low values of the input-output coefficient and intermediate values of the transport rate, particularly if the countries are very asymmetric in size. Otherwise, we obtain agglomeration either in the low cost country (when the transport rate is low) or in the large market (when the transport rate is high). Multiple agglomerated equilibria arise when the transport cost of the intermediate good is significant.